The Hikmah Method in Al-Qur'an - Ibrahim Cek Nuh; Usman Haji Thalib (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2005)
One of the Islamic Dakwah methods that is used in inviting people to do somethings by implementing "Hikmah" which means wisdom. The word "hikmah" is used in the holy Quran only several times. Therefore, it makes "ulama" or scholars work hard to get its meanings so that dai (the callers) know it clearly Thus they are able to call like what Quran instructions stated and they can finally reach the goal The word hikmah, as the linguists say, has a number of meanings namely justce nowledge, patienoe. every speech related to the fact etc Whatever the meanrgs it had better for the caller who uses hikmah as his method keep reating the people gently, changing something gradualy and making prority fasks